Digital technologies and the enhancement of education - MERIGUI, Sara; NEBEG, Zohra; NEBEG, Aimed; HADJADJ, Ahmed (The International tax journal, 2026)
This scholarly contribution is situated within the priority of highlighting the importance of a highly significant area of inquiry in the field of education and its relationship to educational digitalisation: the impact of employing modern, or digital, technologies on the development of teaching and learning practices among learners. The study, therefore, focuses on contemporary technologies in terms of their significance, given that they possess a range of characteristics and advantages that enable the achievement of the intended objectives of the teaching–learning process, which educational systems worldwide aspire to realise in terms of quality and modernity. Such technologies can also foster the development of learners' scientific, cognitive, and experiential skills and competencies. The discussion further outlines the principal foundations and criteria that teachers should consider. The time has come to modernise educational institutions, given the considerable importance of these technologies. Moreover, today's generation must keep pace with ongoing developments across diverse scientific fields; accordingly, from this perspective, an illiterate person lacks proficiency in using such tools and technologies, including the internet and computers. In the view of many, the failure to integrate modern technologies into the teaching–learning process constitutes one of the most pressing problems facing contemporary Algerian schooling,,,